Research methods in deportation: the power-knowledge approach - Radziwinowiczówna, Agnieszka (Edward Elgar Publishing, 2024)
"This prescient book explores how to confront the methodological and ethical challenges in researching deportation. Agnieszka Radziwinowiczowna introduces a 'power-knowledge' approach, crucially taking into account the power imbalances that emerge at every stage of the deportation research process. Bringing together a diverse group of eminent deportation scholars, Research Methods in Deportation makes methodological recommendations on the recruitment of research participants, the inclusion of underrepresented demographic groups, longitudinal research into deportations and co-dissemination. The proposed power-knowledge approach counters the existing positivist paradigm that seeks to extract data from research participants, instead prioritising participants' agency and including them in knowledge co-production. Chapters cover the challenges in researching violent deportation practices and negotiating access for research post-deportation, the methodological challenges of bilingual research in prison, white privilege and the involution of deportation research. This book will be essential reading for students, academics and researchers in migration studies, refugee studies, sociology, anthropology, and social policy. Offering concrete methodological guidance and advice, it will also be beneficial for practitioners in non-governmental organisations conducting research among potentially deportable and deported people"--